Sisterhood heals : the transformative power of healing in community - Bradford, Joy Harden (Ballantine Books, 2023)
"A groundbreaking exploration of how to harness concepts from group therapy and the safety (and joy) of sisterhood to heal yourself and your relationships, from the licensed clinical psychologist who founded the award-winning podcast Therapy for Black Girls. There's an unlimited supply of books, articles, and listicles about how to work on a relationship and grow with a partner, but there are far fewer resources about what healthy growth looks like within a friendship. Dr. Joy Harden Bradford is here to change that. Healing through gathering is Dr. Joy's life's work; she founded Therapy for Black Girls, creating a space to make mental health topics more relevant and accessible for Black women and girls. Now, she dives into the wisdom of group therapy to help Black women strengthen and evolve within our sisterhoods. In Sisterhood Heals, Dr. Joy illustrates how concepts from group therapy are relevant to our lives, whether we realize it or not. She demonstrates how our real-life sister circles function in similar ways to the ones formed in group therapy. In Sisterhood Heals, Dr. Joy unearths the foundations of our connections, reveals the role of attachment theory in our friendships, offers solutions to rebuild after there has been a rupture in a friendship, and shares strategies for taking care of ourselves after a friendship ends. Drawing on her years of clinical experience, Dr. Joy provides actionable advice and scripts we can use to navigate difficult conversations and foster relationships that are not only positive, but transformative. With warmth, wisdom, and empathy, Dr. Joy reminds us that sisterhood is often a lifeline during difficult times and has the power to help us experience increased mental wellness and fuller, more satisfying lives"--